Morbidity and Drug Prescription Audits of General Medicine OPD using WHO Prescribing Indicators in Province 1, Nepal - Shah, Shambhu; Dahal, Prasanna; Sah, Anil Kumar; Parajuli, Surya; Shrestha, Naveen (Europasian Journal of Medical Sciences, 2025)
Background: Periodic assessment of morbidity and drug use at various levels of the healthcare delivery system is important to recognize common prevalent morbidities and rationalize the use of medicines. The study was conducted to determine the common morbidities and audit prescription of general medicine outpatients using the WHO prescribing indicator in government-operated tertiary care zonal hospitals of eastern Nepal. Methods: A cross-sectional study was carried out in two government zonal hospitals of Province 1, Nepal, between March 2019 to August 2019. For analysis, descriptive statistics were used to evaluate prescription characteristics. Prescribing characteristics were evaluated using recommended guidelines of the World Health Organization (WHO) prescribing indicators. Bivariate analysis was performed to compare prescription characteristics between hospitals. P<0.05 was considered statistically significant. Results: Six hundred prescriptions were analyzed. The most prevalent morbidity was endocrine, nutrition & metabolic diseases (21.5%) followed by diseases of the respiratory system (19.8%), circulatory system (17.6%), and digestive system (12.8%). The most frequently encountered individual disease entity were hypertension (18.7%), diabetes (15.5%), acid peptic disorders (14%). A total of 2072 drugs were prescribed with an average of 3.45 (± 1.39) drugs per consultation. About 30.2% of prescriptions encountered contain at least one antibiotic, whereas injectables were prescribed in 1.8%. Only 3.9% of total medicines were prescribed in generic name and 31.7% of drugs prescribed were from the essential medicine list. Bivariate analysis showed that there was a significant difference in prescription encounters with antibiotics and generic prescribing between the two hospitals (p < 0.001). Conclusion: Among the prescriptions evaluated, diseases of the endocrine, respiratory, cardiovascular, and gastrointestinal systems were the most common morbidities. Polypharmacy was prevalent to some extent whereas prescribing in generic and essential medicine lists was poor relative to standard WHO recommendations. However, the overall prescribing of antibiotics and injection was found to be satisfactory.